The why of consumption : contemporary perspectives on consumer motives, goals, and desires - Ratneshwar, S.; Mick, David Glen.; Huffman, Cynthia (London ; New York : Routledge, 2003)
This book brings together an international collection of authors from a variety of disciplines who offer new and critical perspectives, summarize key findings and provide important theoretical frameworks to guide the reader through the 'why?' of consumption. The book answers questions such as: What is the nature of motives, goals, and desires that prompt consumption behaviours? Why do consumers buy and consume particular products, brands and services from the multitude of alternatives afforded by their environments? How do consumers think and feel about their cravings? Unique in focus and with multifaceted approach which anyone interested in consumption and consumer research will find fascinating, this topical book provides an excellent overview of current research, and imparts key insights to illuminate the subject for both academics and practitioners alike.
Introduction : the "why" of consumption / S. Ratneshwar, David Glen Mick, and Cynthia Huffman -- Consumer goal structures and goal-determination processes : an integrative framework / Cynthia Huffman, S. Ratneshwar, and David Glen Mick -- The role of emotions in goal-directed behavior / Richard P. Bagozzi [and others] -- Minimizing negative emotion as a decision goal : investigating emotional trade-off difficulty / Mary Francis Luce, James R. Bettman, and John W. Payne -- The role of approach/avoidance asymmetries in motivated belief formation and change / Frank R. Kardes and Maria L. Cronley -- The missing streetcar named desire / Russell W. Belk, Güliz Ger, and Søren Askegaard -- Postmodern consumer goals made easy!!!! / Craig J. Thompson -- Authenticating acts and authoritative performances : questing for self and community / Eric J. Arnould and Linda L. Price -- Representations of women's identities and goals : the past fifty years in film and television / Elizabeth C. Hirschman and Barbara B. Stern -- The urge to buy : a uses and gratifications perspective on compulsive buying / Ronald J. Faber -- On selling brotherhood like soap : influencing everyday disposal decisions / Luk Warlop, Dirk Smeesters, and Piet Vanden Abeele -- Timestyle and consuming time : why we do what we do with our time / June Cotte and S. Ratneshwar -- Using narratives to discern self-identity related consumer goals and motivations / Jennifer Edson Escalas and James R. Bettman -- The power of metaphor / Robin Coulter and Gerald Zaltman -- Lattice analysis in the study of motivation / Steven Brownstein [and others] -- More than a rat, less than God, staying alive / Jerome B. Kernan -- Four questions about consumer motivation research / Dennis W. Rook.
Originally published 2000 by Routledge.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Consumer behavior; Consumers -- Research; Consommateurs -- Comportement; Consommateurs -- Recherche; BUSINESS & ECONOMICS -- Consumer Behavior; Consumer behavior; Consumers -- Research